Information Source Influence Destination Image - Jamaludin, Mazlina; Aziz, Azlizam; Yusof, Abdul Raheem Mohamad; Idris, Nur Hafizah (International Journal of Independent Research Studies, 2013)
This study examines the relationship between information sources and destination image as well as the relationship between destination image and overall satisfaction among local visitors using structured questionnaires. Structural equation modeling using AMOS was conducted by fitting the data to the hypothesized model using the covariance matrix. Results indicate that induced information sources are important predictor in destination image in addition to influencing overall visitors satisfaction level. This study revealed and confirmed the existing of causal relationships between information sources and destination image which directly lead to positive visitors satisfaction.